Exposure to air pollution and risk of haematological malignancies: a systematic review and dose-response meta-analysis of epidemiologic evidence - Kangqian Lin; Guoxiu Zhou; Hong Guo; Qiang Niu; Heng Guo; Guanling Song; Yunhua Hu; Jiaming Liu; Yizhong Yan (Environmental Research Letters, 2023)
Quantifying the potential association between air pollutants exposure and haematological malignancies (HM) risk can provide more direction for its prevention. In this systematic review and meta-analysis, case-control and cohort studies looked at the association between air pollution and the risk of HM in the general population were included. PubMed, Web of Science, Wanfang database, and China National Knowledge Infrastructure were searched as of 14 April 2022. The Mantel–Haenszel random effects model was used to calculate the meta-analysis relative risk (meta-RR). A two-stage random-effects dose-response meta-analysis was performed to estimate the degree of the associations and a dose-response curve was fitted using a restricted cubic spline model, as well as assessed publication bias. This review was registered with International Prospective Register of Systematic Reviews (CRD42022325677). The literature search yielded 7260 articles, and 41 studies were included. Benzene exposure significantly increased the risk of leukaemia (meta-RR 1.24, 95% confidence interval (95%CI) 1.01–1.54). The meta-RR of traffic density, nitrogen dioxide (NO _2 ), particulate matter (PM _2.5 and PM _10 ) and leukaemia were 1.08 (95%CI 0.99–1.17), 1.02 (95%CI 0.96–1.09), 1.05 (95%CI 0.99–1.11), 1.04 (95%CI 0.69–1.56). 1.07 (95%CI 0.93–1.22), 1.01 (95%CI 0.96–1.06), 1.06 (95%CI 0.98–1.14) were the meta-RR of traffic density, NO _2 , PM _2.5 and lymphoma. The meta-RR of NO _2 and multiple myeloma was 1.00 (95%CI 0.92–1.09). Disease subtype, age and region appeared to modify these associations. When residential distance from a main road was less than 300 m, the risk was relatively high and gradually increased with the decrease of the distance; with the increase of NO _2 exposure concentration, the risk of acute myeloid leukaemia (AML) gradually increased, increasing rapidly once NO _2 concentration reached 40 μ g m ^−3 ; with increasing benzene exposure concentration, the risk of AML and acute lymphoblastic leukaemia gradually increased, particularly after the concentration reached 3 μ g m ^−3 . These findings can be used as epidemiological evidence for the causal relationship between air pollutants and HM.